Does Unfairness Hurt Women? The Effects of Losing Unfair Competitions - Stefano Piasenti; Marica Valente; Roel van Veldhuizen; Gregor Pfeifer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
How do men and women differ in their persistence after experiencing failure in a competitive environment? We tackle this question by combining a large online experiment (N=2,086) with machine learning. We find that when losing is unequivocally due to merit, both men and women exhibit a significant decrease in subsequent tournament entry. However, when the prior tournament is unfair, i.e., a loss is no longer necessarily based on merit, women are more discouraged than men. These results suggest that transparent meritocratic criteria may play a key role in preventing women from falling behind after experiencing a loss.
Keywords: C90; D91; J16; C14; 330; competitiveness; gender; fairness; machine learning; online experiment